Hospitalized Children and Opportunities to Vaccinate Vulnerable Populations: An Integrative Literature Review - BejoWolkers, Paula Carolina; Santos, Jaqueline Silva; Carvalho Furtado, Maria Cândida de; Pina, Juliana Coelho; Garcia Lima, Regina Aparecida; de Mello, Débora Falleiros (International Journal of Pediatrics and Child Health, 2016)
The present study aimed to identify evidence available in the health literature concerning the immunization of hospitalized children. This is a descriptive study based on an integrative literature review. Nine scientific papers published between 2001 and 2013 were analyzed. The results were organized into three themes: opportunities to vaccinate hospitalized children; factors against immunizing hospitalized children; and strategies and interventions to improve child vaccination coverage. Hospitalization is an opportunity to identify factors related to why parents do not vaccinate their children and then implement strategies, such as educational interventions, records-updating, immunization reminders, and providing guidance after hospital discharge.